Low-cost Sieverts-type apparatus for the study of hydriding/dehydriding reactions. (October 2018) - Carrillo-Bucio, Juan Luis; Tena-Garcia, Juan Rogelio; Armenta-Garcia, Eduardo Paul; Hernandez-Silva, Osiry; Cabañas-Moreno, José Gerardo; Suárez-Alcántara, Karina
Graphical abstract: Highlights: Use of twin-lines (sample and reference), to eliminate small thermal effects. Use of a Δp = Δpsample − Δpreference approach in calculations. Eliminate the need of a differential pressure transducer and reduce costs. Abstract: The design and construction of a low-cost equipment for the study of hydriding/dehydriding reactions of different materials are presented. This is a Sieverts-type apparatus where a small amount (0.2–1 g) of solid hydrogen storage materials can be characterized. The apparatus combines the features of double lines (sample and reference) to eliminate small thermal effects on the reservoir and sample-holder volumes, with a Δp = Δpsample − Δpreference approach to eliminate the need of a differential pressure transducer and to reduce costs. This apparatus can work from vacuum to 10 MPa hydrogen pressure and from room temperature to 673 K. Pressure, temperature and volume data are transformed by a real gases equation state and mass balance into hydrogen uptake or release in wt%. Characterization of typical hydrogen storage materials such as LiAlH4 and Mg is presented to validate the performance of the apparatus.